pH Sensor Based on Dual Gate Organic Field Effect Transistor (International Journal of Innovative Research in Computer Science & Technology, 2023)
Nowadays, Organic semiconductors  (OSCs) are receiving increasing attention these days  because they have many attractive properties – including  light weight, low-cost production, low- temperature  processing, mechanical flexibility, and abundant  availability. Earlier, ISFET ( The ion sensitive field effect  transistor) was used as a sensing device. It is used in  measuring ion concentrationin the solution. It is based on  inorganic field effect transistors where an electrolyte  solution and ion- sensitive membrane is embedded. It is a special type of MOSFET in which gate electrode was replaved by refrence electrode and ion-sensistive layer. There are various categories of ISFET such as PH-ISFET, CHEM-ISFET, BIO-ISEFT etc. As these devices have  many advantages,they show good compatibilitywith the CMOS technology ,controlling procesveprecisely,operates at equilibrium conditions,capable of  showing label free detection and easy to use, still these  devices suffer from few innate deficiency.In case of long term use they are unrelible , unstable due to ionic damage  and shouldhave low SNR. For sensing purpose, the main principle involves a variation in the surface capacity that occurs due to ionic interactions at the electrolye/gate  oxide. ISFET main constraint lies in the the poor sensing  margin within the Nernstian limit (59 mV per pH) at room  temperature and this has gained much research attention  over the past few decades.So,diffedrent devices have been  tried till now to improve the sensing margin(>59 mV per  pH) and hence this results in different device design with different configurations .We also proceeded our work with  the same aim to improve the Nernestian limit using  Organic Field Effect Transistor as device and hence tried  different configurations to get thedesired results.In our  work, we have developed a dual gate organic field effect  transistor (DG-OFET) based pH sensor that will be able to  detect the variations in the aqueous (electrolyte)  medium.In this structure source sided underlap technique with dual gate sensing approach has been used.The simulationresults were extracted with the help of software  package Silvaco TCAD-ATLAS.The simulated results display that the proposed DG-OFET shows significantly higher sensitivity for different dielectrics.
Keywords: ISFET; Organic Field Effect Transistors; DG-OFET; Nernestian Limit